Herpes zoster in general practice - Ross, Constance A. C. (1975)
Eighty-seven patients with the clinical diagnosis of herpes zoster were seen during a one-year period in eight general practices in Glasgow, the rate per 1,000 practice population being approximately 2·4. Of these, 78 (90 per cent) had serological evidence of active infection with herpes zoster. The anatomical location of the skin eruption was most common in the areas of the fifth cranial nerve, middle and lower trunk and thigh. A possible reactivating agent (trauma four, steroids two, irradiation one) was found in only seven patients. The illness as assessed by systemic upset and dissemination of lesions was generally not severe. Post-herpetic neuralgia was the most troublesome complication, found in 44 per cent of 64 patients revisisted 3-18 months after the acute illness.